Diet-gut microbiome interaction and its impact on host blood glucose homeostasis: a series of nutritional n-of-1 trialsResearch in context - Yuanqing Fu; Wanglong Gou; Haili Zhong; Yunyi Tian; Hui Zhao; Xinxiu Liang; Menglei Shuai; Lai-Bao Zhuo; Zengliang Jiang; Jun Tang; Jose M. Ordovas; Yu-ming Chen; et al. (EBioMedicine)
Summary: Background: The interplay between diet and gut microbiome substantially influences host metabolism, but uncertainties remain regarding their relationships tailored for each subject given the huge inter-individual variability. Here we aim to investigate diet-gut microbiome interaction at single-subject resolution and explore its effects on blood glucose homeostasis. Methods: We conducted a series of nutritional n-of-1 trials (NCT04125602), in which 30 participants were assigned high-carbohydrate (HC) and low-carbohydrate (LC) diets in a randomized sequence across 3 pair of cross-over periods lasting 72 days. We used shotgun metagenomic sequencing and continuous glucose monitoring systems to profile the gut microbiome and blood glucose, respectively. An independent cohort of 1219 participants with available metagenomics data are included as a validation cohort. Findings: We demonstrated that the gut microbiome exhibited both intra-individually dynamic and inter-individually personalized signatures during the interventions. At the single-subject resolution, we observed person-specific response patterns of gut microbiota to interventional diets. Furthermore, we discovered a personal gut microbial signature represented by a carb-sensitivity score, which was closely correlated with glycemic phenotypes during the HC intervention, but not LC intervention. We validate the role of this score in the validation cohort and find that it reflects host glycemic sensitivity to the personal gut microbiota profile when sensing the dietary carbohydrate inputs. Interpretation: Our finding suggests that the HC diet modulates gut microbiota in a person-specific manner and facilitates the connection between gut microbiota and glycemic sensitivity. This study represents a new paradigm for investigating the diet–microbiome interaction in the context of precision nutrition. Funding: This work was supported by the National Key R&D Program of China, National Natural Science Foundation of China and Zhejiang Provincial Natural Science Foundation of China.